Oil exports and the Iranian economy - Hadi Salehi Esfahani; Kamiar Mohaddes; Mohammad Hashem Pesaran (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper develops a long run growth model for a major oil exporting economy and derives conditions under which oil revenues are likely to have a lasting impact. This approach contrasts with the standard literature on the Dutch disease and the resource curse, which primarily focus on short run implications of a temporary resource discovery. Under certain regularity conditions and assuming a Cobb Douglas production function, it is shown that (log) oil exports enter the long run output equation with a coefficient equal to the share of capital. The long run theory is tested using a new quarterly data set on the Iranian economy over the period 1979Q1-2006Q4. Building an error correction specification in real output, real money balances, inflation, real exchange rate, oil exports, and foreign real output, the paper finds clear evidence for two long run relations: an output equation as predicted by the theory and a standard real money demand equation with inflation acting as a proxy for the (missing) market interest rate. Real output in the long run is shaped by oil exports through their impact on capital accumulation, and the foreign output as the main channel of technological transfer. The results also show a significant negative long run association between inflation and real GDP, which is suggestive of economic inefficiencies. Once the effects of oil exports are taken into account, the estimates support output growth convergence between Iran and the rest of the world. We also find that the Iranian economy adjusts quite quickly to the shocks in foreign output and oil exports, which could be partly due to the relatively underdeveloped nature of Iran's financial markets.
Keywords: C32; C53; E17; F43; F47; Q32; 330; growth models; long run relations; Iranian economy; oil price and foreign output shocks; error correcting relations; Mineralölwirtschaft; Erdöl; Export; Einnahmen; Wirtschaftswachstum; Mineralölpreisschock; Makroökonomischer Einfluss; Dutch Disease; Iran